Credibility on the web: a study of the credibility of consumer information on Malaysian e-commerce websites / Dr. Kiranjit Kaur …[et al.] - Kaur, Kiranjit (Dr.); Iyer, Mangalam Gopala; Abdul Jabar, Noraziah; Abdul Hamid, Norliza (2004)
This study examines the credibility of e-commerce websites based on the clarity and accessibility of information that allows consumers to make an informed decision about the value of the information available on the site. The contents of 60 Malaysian registered websites dealing with products, services and health products were investigated with the guide of a coding instrument over a period of two months. The results show that the majority of the websites were not credible as they did not contain sufficient information on claims, disclaimers and warnings, guarantees, market coverage, timeliness, source of information/advice, authority and credentials, commercial influences, protection of privacy and personal information, as well as information on cancellation, return, delivery and payment terms, which were considered to be important in assessing credibility. Thus, consumers need to check on the site's background and the reliability of information provided. Retailers on the other hand, need to promote credibility and to ensure compliance of consumer protection laws and policies. The government too must play a role to ensure that businesses comply with existing laws, otherwise take action where necessary, encourage further research on this area, and educate consumers on their rights and responsibilities.